Meningkatkan Kemampuan Bahasa Ekspresif Menggunakan Terapi Applied Behavior Analysis (ABA) Pada Anak Attention Deficit Hyperactivity Disorder (ADHD) - Putri Dewi Cahyani; Defi Astriani; Devia Purwaningrum (Program Studi Bimbingan Konseling Islam, Fakultas Tarbiyah Dan Ilmu Keguruan, Institut Ummul Quro Al-Islami Bogor, 2026)
In terms of communication, Children with Attention Deficit Hyperacitivity Disorder (ADHD) have difficulty with expressive language. As a result, children will have difficulty in communication and interaction with others. This study aims to improve expressive language in children with Attention Deficit Hyperactivity Disorder (ADHD). One of the interventions used in improving expressive language in ADHD children is Applied Behavior Analysis (ABA) therapy. ABA therapy is a method of providing material to children that is delivered firmly, without encouragement, pressure, and appreciation in return. This therapy is modified using flashcard media which aims to increase children's functional vocabulary. The research method used is single subject experiment with A-B-A design. The sampling technique used purposive non probability technique. The research subject amounted to 1 child with Attention Deficit Hyperactivity Disorder (ADHD) type combination disorder aged 4-5 years. The results showed that the subject experienced an increase in understanding labeling, namely labeling surrounding objects, limbs, and places after being treated. Thus it can be concluded that Applied Behavior Analysis (ABA) therapy can improve expressive language in Attention Deficit Hyperactivity Disorder (ADHD) children.